(untitled) (Hackensack, N.J., 2004)
The huge amount of data obtained by surveys in all wavebands, from radio to X-rays, has allowed major progress in the understanding of Active Galactic Nuclei and of their cosmic evolution. This book contains the proceedings of a conference intended to give a broad overview of the recent results obtained by recent AGN surveys over the whole electromagnetic spectrum. Topics which were discussed during the conference and are included in this volume are: AGN evolution, contribution to the cosmic background, AGN luminosity functions in different wavebands, multiwavelength properties of AGN, unified model and unconventional AGN, connection with the host galaxies, co-evolution of AGN and galaxies, implications for the local density of supermassive black holes. Future AGN surveys planned with forthcoming new observational facilities are also included.
Keywords: Active galactic nuclei,Hoạt động trung tâm thiên hà